Secondary crystallization kinetics. Issue 2 (12th September 2018) - Hay, James N.
Abstract: The overlap between primary and secondary crystallization is the cause of the repeated observations of fractional constant n values, of no theoretical significance, in the analysis of polymer crystallization by the Avrami equation. The time dependence of the growth nuclei in primary and secondary crystallization are explained in terms of reptation and nucleation theory. A composite equation involving both primary and secondary crystallization has been derived to account for the development of the total fractional crystallinity, X t, with time, X t  =  X p, ∞ (1–exp (– Z p t n ).(1 +  k s t 1/2 ) and procedures derived for determining the rate constants, Z p and k s, and the limiting fractional crystallinity of the primary process, X p, ∞, such that they are not treated as adjustable parameters. The fit of the equation to experimental crystallinity/time data was within experimental error. This interpretation accounted for n values in excess of those expected for the crystallization mechanisms adopted in deriving the Avrami equation but values >3.5 and <4.0 are attributed to the presence of induction times due to homogeneous primary nucleation of the lamellae. Evidence is presented for the presence of two simultaneous processes, primary and secondary, in the crystallization of polymers, which occur with different mechanisms and are readily distinguished by their dependence on time: an exponential increase and an increase with the square root of time. Differences arise from the critical growth nuclei, whose growth is limited by chain entanglements in the case of primary and local reptation in the case of secondary. Abstract : Evidence is presented for the presence of two simultaneous processes, primary and secondary, in the crystallization of polymers, which occur with different mechanisms and are readily distinguished by their dependence on time: an exponential increase and an increase with the square root of time. Differences arise from the critical growth nuclei, whose growth is limited by chain entanglements in the case of primary and local reptation in the case of secondary.